2015
DOI: 10.1007/s40145-015-0160-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural and photoluminescent properties of the MgGa2O4:Co2+ ceramic compound revisited after two decades

Abstract: Abstract:In this work, we revisit and show how the structural and photoluminescent properties of the MgGa 2 O 4 ceramic compound have been kept unchanged for more than two decades. The obtained results confirm the high quality, radiative efficiency, and chemical stability of this ceramic, proving that the material is a strong candidate to be used in optical device applications with relatively long useful life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In its opaque state, it has various applications, including electronics, energy production, and spintronics [1,2], but the most interesting applications are those that exploit the fact that transparency (in the single crystal state) can be coupled with n-type electronic conductivity [1,3]. For instance, photodetectors, gas sensors, transparent electrodes, solid-state phosphors, waveguides, LEDs, or lasing ion hosts (operation at < 100 K) may be derived from this material [3][4][5][6][7]. Moreover, owing primarily to the partially inverted character of its cubic lattice, MgGa 2 O 4 is a useful host for transition metal (TM) cation dopant spectroscopy (see Section 2).…”
Section: Introduction mentioning
confidence: 99%
“…In its opaque state, it has various applications, including electronics, energy production, and spintronics [1,2], but the most interesting applications are those that exploit the fact that transparency (in the single crystal state) can be coupled with n-type electronic conductivity [1,3]. For instance, photodetectors, gas sensors, transparent electrodes, solid-state phosphors, waveguides, LEDs, or lasing ion hosts (operation at < 100 K) may be derived from this material [3][4][5][6][7]. Moreover, owing primarily to the partially inverted character of its cubic lattice, MgGa 2 O 4 is a useful host for transition metal (TM) cation dopant spectroscopy (see Section 2).…”
Section: Introduction mentioning
confidence: 99%
“…For example, we investigated the compound MgGa 2 O 4 :Co 2+ obtained through the solid-state method for the first time in 1992. More than two decades later, it was observed that the structural and photoluminescent properties of the MgGa 2 O 4 :Co 2+ sample remained unchanged 14 .…”
Section: Introductionmentioning
confidence: 99%